METHODS OF TEACHING STUDENTS TO CREATE COMPUTER GAMES - Shekerbekova , Ш.Т.; Izabaevad. , Д.Н.; Til'ubergenov , М.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article considers the methodology of teaching schoolchildren to create computer games. Initially, the concept of a game is described, the basic didactic requirements for the creation of a game are given and a more broad characteristic of the concept of "computer game" is given. Methods of using computer games in teaching computer science, as well as the classification of computer games. Describe the features of using computer games in educational space. To create computer games it is recommended to use game designers, and for their creation it is enough to learn to use game designers. Of the several proposed constructors, only one of the editors of 2D-constructor Game Maker Studio is used. Game Maker Studio describes the methods of creating games. Initially, the concept of sprite, object, level, event, action, used in the general game, and then the idea of creating a game is described. The script of the game in the Game Maker Studio Editor is given the possibility of creating games.